A thermodynamic investigation of the cellulose allomorphs: Cellulose(am), cellulose Iβ(cr), cellulose II(cr), and cellulose III(cr). (February 2015) - Goldberg, Robert N.; Schliesser, Jacob; Mittal, Ashutosh; Decker, Stephen R.; Santos, Ana Filipa L.O.M.; Freitas, Vera L.S.; Urbas, Aaron; Lang, Brian E.; Heiss, Christian; Ribeiro da Silva, Maria D.M.C.; Woodfield, Brian F.; Katahira, Rui; et al.
Graphical abstract: Highlights: Cellulose allomorphs were prepared and carefully characterized. Measurements by oxygen bomb calorimetry, solution calorimetry, and by PPMS. Thermodynamic properties for interconversion reactions of the cellulose allomorphs. Review of the earlier literature with recalculation of property values. Standard thermodynamic formation properties. Abstract: The thermochemistry of samples of amorphous cellulose, cellulose I, cellulose II, and cellulose III was studied by using oxygen bomb calorimetry, solution calorimetry in which the solvent was cadoxen (a cadmium ethylenediamine solvent), and with a Physical Property Measurement System (PPMS) in zero magnetic field to measure standard massic heat capacities C p, w ∘ over the temperature range T = (2 to 302) K. The samples used in this study were prepared so as to have different values of crystallinity indexes CI and were characterized by X-ray diffraction, by Karl Fischer moisture determination, and by using gel permeation chromatography to determine the weight average degree of polymerization DP w . NMR measurements on solutions containing the samples dissolved in cadoxen were also performed in an attempt to resolve the issue of the equivalency or non-equivalency of the nuclei in the different forms of cellulose that were dissolved in cadoxen. While large differences in the NMR spectra for the various cellulose samples in cadoxen were not observed, one cannot be absolutely certain that these cellulose samples are chemically equivalent in cadoxen. Equations were derived which allow one to adjust measured property values of cellulose samples having a mass fraction of water w H 2 O to a reference value of the mass fraction of water w ref . The measured thermodynamic properties (standard massic enthalpy of combustion Δ c H w ∘, standard massic enthalpy of solution Δ sol H w ∘, and C p, w ∘ ) were used in conjunction with the measured CI values to calculate values of the changes in the standard massic enthalpies of reaction Δ r H w ∘ ∗, the standard massic entropies of reaction Δ r S w ∘ ∗, the standard massic Gibbs free energies of reaction Δ r G w ∘ ∗, and the standard massic heat capacity Δ r C p, w ∘, for the interconversion reactions of the pure ( CI = 100) cellulose allomorphs, i . e ., cellulose(am), cellulose I(cr), cellulose II(cr), and cellulose II(cr), at the temperature T = 298.15 K, the pressure p ∘ = 0.1 MPa, and w H 2 O = 0.073. The " ∗ " denotes that the thermodynamic property pertains to pure cellulose allomorphs. Values of standard massic enthalpy differences Δ 0 T H w ∘, standard massic entropy differences Δ 0 T S w ∘, and the standard massic thermal function Φ w ∘ = Δ 0 T S w ∘ - Δ 0 T H w ∘ / T were calculated from the measured heat capacities for the cellulose samples and for the pure cellulose allomorphs. The extensive literature pertinent to the thermodynamic properties of cellulose has been summarized and, in many cases, property values have been calculated or recalculated from previously reported data. The thermodynamic property data show that cellulose(am) is the least stable of the cellulose allomorphs considered in this study. However, due to the uncertainties in the measured property values, it is not possible to use these values to order the relative stabilities of the cellulose (I, II, and III) crystalline allomorphs with a reasonable degree of certainty. Nevertheless, based on chemical reactivity information, the qualitative order of stability for these three allomorphs is cellulose III(cr) > cellulose II(cr) > cellulose Iβ(cr) at T = 298.15 K. However, as evidenced by the fact that cellulose I(cr) can be reformed by the application of heat and water to a sample of cellulose III(cr), the differences in the stabilities of these three allomorphs appear to be small and may be temperature dependent. Standard thermodynamic formation properties as well as property values for the conversion reactions of the cellulose allomorphs to α-d -glucose(cr) have been calculated on the assumption that S w ∘ → 0 as T → 0 . The values for the standard massic Gibbs free energy of reaction Δ r G w ∘ for the conversion of the cellulose allomorphs to α-d -glucose(cr), with the exception of anhydrous cellulose(am), all have positive values and thus are thermodynamically not favored for mass fractions of water w H 2 O < 0.073.